The Power of Information: Impact of Knowledge Sharing Agri Portals in Rural India - Kiran Yadav; Gyanendra Sharma (Journal of Agricultural Extension Management, 2013)
In agriculture and rural development, a variety of fairly large-scale and mature ICT-enabled projects are providing social and economic value all along the agro-value chain by filling the information gap for the farmers. Such projects, directly linked to income-generating activities, have visible direct economic value for end-users. The large projects have impact on up to several million rural dwellers, while benefiting all actors of rural development. However, the impact assessment of these projects is still an open issue in terms of methodology and results, which leads to failure of many such ICT initiatives especially in agriculture. The present study is an effort towards assessing two such ICT initiatives in agriculture launched by the Government of India